Ranaviruses : lethal pathogens of ectothermic vertebrates - Gray, Matthew J.; Chinchar, V. Gregory (Springer International Publishing : Imprint: Springer, 2015)
The first book of its kind, this work discusses the global extent of ranaviruses, principles of ranavirus ecology and evolution. The research included provides guidance on designing ranavirus surveillance studies to determine risk. Ranaviruses are are double-stranded DNA viruses that cause hemorrhagic disease in amphibians, reptiles, and fish. Ranaviruses have caused mass die-offs of ectothermic vertebrates in wild and captive populations around the globe. Ranaviruses: Lethal Pathogens of Ectothermic Vertebrates serves an urgent need to assemble the contemporary information on ranaviruses, and provide guidance on how to assess this threat in populations.